What is the best initial antibiotic regimen for patients hospitalized with an MRSA cellulitis?. Issue 2 (February 2017) - Walden, Jeffrey
Abstract : EVIDENCE‐BASED ANSWER : The answer is not entirely clear. However, for methicillinresistant Staphylococcus aureus (MRSA) skin and soft tissue infections (SSTIs), linezolid has a higher clinical cure rate and decreased length of stay than vancomycin (SOR: A, systematic review of RCTs). Daptomycin is associated with faster clinical resolution and fewer days of inpatient therapy than vancomycin in patients with SSTIs and risk factors for MRSA (SOR: B, cohort study). Vancomycin, linezolid, daptomycin, telavancin, and clindamycin are all acceptable antibiotic regimens for patients hospitalized with MRSA cellulitis (SOR: C, expert consensus).